2011
DOI: 10.1124/jpet.111.180661
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Pharmacology and Toxicology Evaluation of Polyethylene Glycol-Conjugated Interferon β-1a

Abstract: Human interferon (IFN) ␤ has well established beneficial effects in treating relapsing forms of multiple sclerosis, but current first-line treatment requires frequent (from daily to weekly) parenteral administration. A 20-kDa polyethylene glycol (PEG)-conjugated IFN ␤-1a (PEG-IFN ␤-1a) is being developed to decrease the frequency of administration and improve patient convenience and compliance. We present pharmacokinetic (PK) and pharmacodynamic (PD) parameters, immunogenicity, and safety of PEG-IFN ␤-1a in Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
(46 reference statements)
2
23
0
Order By: Relevance
“…limited number showed that the elicited anti-PEG antibodies result in rapid clearance of a subsequent dose of PEGylated protein products: such a phenomenon was observed with PEGylated interferon (IFn) β-1a in Rhesus monkeys, 20) PEGylated urate oxidase in humans, 18) and PEGylated asparaginase in humans. 19) This might in part be due to weak immunogenicity of the anchoring protein for PEG and no attempt to discriminate between anti-PEG antibodies and anti-anchoring protein antibodies.…”
Section: Polyethyleneglycol: a Classical But Innovative Materialsmentioning
confidence: 99%
“…limited number showed that the elicited anti-PEG antibodies result in rapid clearance of a subsequent dose of PEGylated protein products: such a phenomenon was observed with PEGylated interferon (IFn) β-1a in Rhesus monkeys, 20) PEGylated urate oxidase in humans, 18) and PEGylated asparaginase in humans. 19) This might in part be due to weak immunogenicity of the anchoring protein for PEG and no attempt to discriminate between anti-PEG antibodies and anti-anchoring protein antibodies.…”
Section: Polyethyleneglycol: a Classical But Innovative Materialsmentioning
confidence: 99%
“…Unfortunately, while there are nuclear magnetic resonance spectroscopy and gel electrophoresis methods as well as enzyme-linked immunosorbent assay techniques for assessing PEG in tissues or fluids, an analysis of the effects of different HMW PEGs on cellular PEG distribution and PEG-related toxicologic findings has not been done, likely because a PEG IHC technique was unavailable (Cheng et al 2012;Elliott et al 2012;Tsai, Cheng, and Roffler 2001;Webster et al 2009). Recently, anti-PEG antibodies have been developed by several groups and their potential utility as IHC reagents demonstrated in published pharmacology studies (Hu et al 2011;Menkhorst et al 2009;White et al 2007). These antibodies were developed to bind either the PEG molecule itself, the backbone linker of the PEG, or the terminal PEG methoxy group (Cheng et al 2012;Webster et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A short circulatory half-life can necessitate frequent injections, from weekly to daily doses, thus increasing the patient's discomfort, overall expense of the treatment regimen, and risks of patient noncompliance. Although antibody therapies (whole IgG) can persist in circulation for days or weeks because of their large size and recycling via neonatal Fc receptors (FcRns), recombinant cytokines and antibody fragments (e.g., FAb 0 ) commonly persist for much shorter circulation times (typically minutes to hours) [16][17][18]. To increase the plasma half-life, a strategy known as PEGylation was developed, in which the hydrophilic polymer poly(ethylene glycol) (PEG) is covalently conjugated to the therapeutic.…”
Section: Limitations Of Intravenous Delivery Of Biologicsmentioning
confidence: 99%
“…In the successful examples noted earlier, such rapid availability may be necessary to [17]. (b) Comparison of the serum half-lives of PEGylated (square symbols) or non-PEGylated (circle symbols) interferon-b-1a (IFN-b-1a) in rhesus monkeys after intramuscular (filled symbols) or subcutaneous (open symbols) administration [18]. (c, d) Increased serum half-lives of anti-vascular endothelial growth factor (VEGF) and anti-epidermal growth factor receptor (EGFR) antibodies that were engineered (Xtend-VEGF, Xtend-EGFR) for enhanced affinity to neonatal Fc receptor (FcRn) [25].…”
Section: Subcutaneous Administration Of Biologicsmentioning
confidence: 99%